2019
DOI: 10.1557/jmr.2019.149
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of high-pressure torsion-induced shear banding and lamellar thickness saturation in Co–Cr–Fe–Ni–Nb high-entropy composites

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The FCC, BCC, and sigma phases were fixed in the structure. Moreover, the Cr-rich sigma phase was found to be very common in Cr-containing HEAs in sintered powder bulks [47,48], as well as in heat-treated cast alloys [49]. The presence of the sigma phase in the structure of the specimens determines the high values of strength, hardness, and low strain before fracture.…”
Section: Physical and Mechanical Properties Of Consolidated Samplesmentioning
confidence: 99%
“…The FCC, BCC, and sigma phases were fixed in the structure. Moreover, the Cr-rich sigma phase was found to be very common in Cr-containing HEAs in sintered powder bulks [47,48], as well as in heat-treated cast alloys [49]. The presence of the sigma phase in the structure of the specimens determines the high values of strength, hardness, and low strain before fracture.…”
Section: Physical and Mechanical Properties Of Consolidated Samplesmentioning
confidence: 99%
“…Maity et al found that due to the addition of Nb element, the lamellar eutectic morphology fragments of CrCoNb generated would be embedded into the FeCoNiCr single-phase solid solution. The regular lamellar morphology was conducive to improving the structural stability and significantly improving the strength and toughness [5]. Another eutectic point of Co-Cr-Fe-Ni-M (M = Hf, Ta, Nb) system was successfully obtained by Xie et al, and the eutectic composition of the coating was thus changed.…”
Section: Introductionmentioning
confidence: 98%
“…Strengthening of alloys with the fcc phase can be achieved by either grain refinement [31,32,33,34,35,36] or by dispersion strengthening (adding hard particles in the matrix) [37,38,39,40,41]. Grain refinement is one of the effective strengthening strategies that can be achieved in two ways: (i) Changing the processing technique (employ processes with a high cooling rate like additive manufacturing or copper mold casting or melt spinning) [42,43,44,45] or using non-equilibrium processing like the mechanical alloying (MA) [46,47,48] or (ii) Employing thermomechanical processes [25,36,49,50,51]. Mainly, A-HEA-based alloys were strengthened by thermomechanical processing like severe plastic deformation (processing with friction stir processing [25], highpressure torsion [49], etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Grain refinement is one of the effective strengthening strategies that can be achieved in two ways: (i) Changing the processing technique (employ processes with a high cooling rate like additive manufacturing or copper mold casting or melt spinning) [42,43,44,45] or using non-equilibrium processing like the mechanical alloying (MA) [46,47,48] or (ii) Employing thermomechanical processes [25,36,49,50,51]. Mainly, A-HEA-based alloys were strengthened by thermomechanical processing like severe plastic deformation (processing with friction stir processing [25], highpressure torsion [49], etc.). Kumar et al have achieved a yield strength improvement of about 315 MPa by grain refinement (reduction from millimeter to micrometer-range sized grains) [25].…”
Section: Introductionmentioning
confidence: 99%